(untitled) (Tanzania Journal for Population studies and Development, 2023)
Organizations and countries have, in the last one decade or so, been undertaking different efforts and strategies to professionalize monitoring and evaluation as a strategy to improve the quality of its services, and to defend and protect the welfare of commissioners and professionals. This article provides the global trend of professionalization of the field of monitoring and evaluation. The article has generally shown that professionalization of monitoring and evaluation is a necessary strategy for improving the quality of services and products and wider monitoring and evaluation. The adoption of professionalization is determined by a number of factors; and particularly political will, institutionalization, level of maturity of monitoring and evaluation associations and networks, results-based culture, and the maturity of capacity building programmes. Comparatively, North American countries have recorded tremendous achievements in the professionalization of monitoring and evaluation; with Canada reaching the stage of accreditation. Generally in Africa, South Africa, and to a certain extent Ghana, have recorded significant achievements in professionalizing monitoring and evaluation due to the factors just mentioned. In East Africa, the level of monitoring and evaluation professionalization and institutionalization is relatively higher in Uganda and Kenya compared to Tanzania where, despite a few obstacles, there has been a combined effort from the government, TANEA, members of parliament and training institutions to professionalize and institutionalize monitoring and evaluation. Substantial achievement has been made, including – but not limited to – improvement of lobbying and support from both the parliament and the president’s office, increased number of short- and long-term training programmes and atheist partial institutionalization of monitoring and evaluation within the government systems.